SARS-CoV-2 and Glutamine: SARS-CoV-2 Triggered Pathogenesis via Metabolic Reprograming of Glutamine in Host Cells - Bharadwaj, Shiv; Singh, Mahendra; Kirtipal, Nikhil; Kang, Sang Gu (Frontiers in Molecular Biosciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, as coronavirus disease 2019 (COVID-19) pandemic, has killed more than a million people worldwide, and researchers are constantly working to develop therapeutics in the treatment and prevention of this new viral infection. To infect and induced pathogenesis as observed in other viral infections, we postulated that SARS-CoV-2 may also require an escalation in the anabolic metabolism, such as glucose and glutamine, to support its energy and biosynthetic requirements during the infection cycle. Recently, Codo et al., (2020) demonstrated the requirement of altered glucose metabolism in SARS-CoV-2 pathogenesis, but the role of dysregulated glutamine metabolism is not yet mentioned for its infection. In this perspective, we have attempted to provide a summary of possible biochemical events on putative metabolic reprograming of glutamine in host cells upon SARS-CoV-2 infection by comparison to other viral infections/cancer metabolism and available clinical data or research on SARS-CoV-2 pathogenesis. This systematic hypothesis concluded the vital role of glutaminase-1 (GLS1), phosphoserine aminotransferase (PSAT1), hypoxia-inducible factor-1 alpha (HIF-1α), mammalian target of rapamycin complex 1 (mTORC1), glutamine-fructose amidotransferase 1/2 (GFAT1/2), and transcription factor Myc as key cellular factors to mediate and promote the glutamine metabolic reprogramming in SARS-CoV-2 infected cells. In absence of concrete data available for SARS-CoV-2 induced metabolic reprogramming of glutamine, this study efforts to connect the gaps with available clinical shreds of evidence in SARS-CoV-2 infection with altered glutamine metabolism and hopefully could be beneficial in the designing of strategic methods for therapeutic development with elucidation using in vitro or in vivo approaches.